2004
DOI: 10.1007/s00018-004-4009-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of apolipoprotein E in lipid metabolism in the central nervous system

Abstract: The critical roles of apolipoprotein E (apoE) in regulating plasma lipid and lipoprotein levels have been extensively studied for over 2 decades. However, an understanding of the roles of apoE in the central nervous system (CNS) is less certain. This review will summarize the available experimental results on the role of apoE in CNS lipid homeostasis with respect to its modulation of sulfatide trafficking, alteration of CNS cholesterol homeostasis and apoE-induced changes in phospholipid molecular species in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 109 publications
(118 reference statements)
1
52
0
Order By: Relevance
“…ApoE plays a prominent role in the transport and metabolism of plasma cholesterol and TG through its ability to interact with the low density lipoprotein (LDL) receptor and the LDL receptor-related protein (32,33). However, such a role of apoE in the CNS is uncertain, but many studies demonstrated that apoE does not affect the cholesterol mass content or the phospholipid mass levels and composition in the CNS as a whole, although apoE may modulate cholesterol and phospholipid homeostasis in selective subcellular membrane compartments (34). In contrast to such a uncertainty, it has been demonstrated that apoE mediates sulfatide trafficking and metabolism in the CNS (35) and the PNS (Cheng, Jiang and Han, unpublished data).…”
Section: Some Proteins Related To Lipids Play Different Roles In the mentioning
confidence: 99%
“…ApoE plays a prominent role in the transport and metabolism of plasma cholesterol and TG through its ability to interact with the low density lipoprotein (LDL) receptor and the LDL receptor-related protein (32,33). However, such a role of apoE in the CNS is uncertain, but many studies demonstrated that apoE does not affect the cholesterol mass content or the phospholipid mass levels and composition in the CNS as a whole, although apoE may modulate cholesterol and phospholipid homeostasis in selective subcellular membrane compartments (34). In contrast to such a uncertainty, it has been demonstrated that apoE mediates sulfatide trafficking and metabolism in the CNS (35) and the PNS (Cheng, Jiang and Han, unpublished data).…”
Section: Some Proteins Related To Lipids Play Different Roles In the mentioning
confidence: 99%
“…ApoE has been reported to carry out additional functions such as stimulation of cholesterol efflux from macrophages, prevention of platelet aggregation, and inhibition of proliferation of T-lymphocyte and endothelial cells. Its common structural isoforms differentially affect the risk of developing atherosclerosis and neurodegenerative disorders, including Alzheimers's disease (reviewed in Han, 2004;Greenow et al, 2005).…”
Section: Intestine and Miscellaneous Expressionmentioning
confidence: 99%
“…Although the delivery of plasma lipoproteins from the circulation to the CNS is precluded by the blood-brain barrier, the CNS contains a distinct population of high-density lipoproteins that are secreted by glia and contain apolipoprotein E (apoE) as their major apolipoprotein (Han, 2004). ApoE is thought to play an important role in the CNS, because apoE synthesis increases dramatically after injury of either the CNS or peripheral nervous system (Ignatius et al, 1986;Mahley, 1988).…”
Section: Introductionmentioning
confidence: 99%